Memahami Perkembangan Peserta Didik dan Hukum Hukum Perkembangan - Habsy, Bakhrudin All; Jatmiko, Maia Rahmanindia Putri; Sari, Siska Amelia; Sari, Fauziah Ardelia (TSAQOFAH, 2024)
The students' differences lie in their thinking patterns, imagination, intelligence, and workmanship. before learning specifically about students, it is necessary to see the development of students' participation. The purpose of this study is to understand the development of students and the laws of development. Methods used are literature studies, with methods of collecting library data, reading, recording, and managing research materials. The result obtained under the definition of a Student development is a period when there is a process of change in individuals both physically and psychologically mentally that takes place continuously and will affect the formation of the personality of the individual. And in this period of development it is very important to instill the personality character of the Indonesian nation. The purpose of student development is to develop abilities, understand the nature of student growth and development starting at an early age, elementary, secondary, and adult. The development of students has three aspects: development, emotional development, and intelligence/cognitive development. The principles of law generally describe that the process of development occurs regularly, cythemically, gradually and does not occur suddenly and is influenced by certain factors. It is also explained in the principles of student development, that each individual experiences a different development from the other and occurs differentially and integrally.